Models of bridge lane direction specification - Caccetta, Louis; Foulds, L.; Rumchev, Ventseslav (Yokohama Publishers, 2007)
An important matter in the management of some freeways that include a city bridge is specifying the direction of the bridge lanes in each time period of a given, congested planning horizon. We propose and analyse some dynamic optimisation models and solution techniques for this problem.